Creative Melanchthonism: The Limits of Cultural Exchange Research on the Example of Academic Humanism in the Second Half of the Sixteenth Century - Storchová, Lucie (Dějiny – teorie – kritika, 2019)
This study investigates possible reasons underlying the motivation of the older generation of Czech researchers who despite plentiful source materials showed little interest in a specific case of cultural exchange, namely one that took place after mid-sixteenth century between Czech scholars and German Lutheran universities. The subject of this exchange was the natural philosophy of Philipp Melanchthon and its adaptation to a new cultural environment, mainly that of the Prague Utraquist university. The author points to various cultural and ideological factors which may have contributed to underrepresentation of this cultural exchange in nineteenth- and twentieth-century Czech historiography. In particular, while humanist scholarship was perceived as a positive cultural value, nationalist Czech historians found it difficult to reconcile this with their notion of the German ‘civilising mission’ and tended to focus on links to the Italian environment. It is also well possible that some religious factors played a role or attempts to play down various forms of ‘trivialisation’. Czech historians may have been indebted to the modern system of sciences classification and had certain preconceptions regarding ‘suitable sources’ that would better suit their notion of forms of knowledge and mediation of cultural exchange in Early Modern Era.